Computed Tomography-Guided Transfissural Coil Localization of Lung Nodules - Xia, Feng-Fei; Shi, Yi-Bing; Wang, Tao; Fu, Yu-Fei (The Thoracic and Cardiovascular Surgeon, 2019)
Background The objective of this study was to evaluate the feasibility, safety, and clinical effectiveness of preoperative computed tomography (CT)-guided transfissural coil localization (TFCL) of subfissural lung nodules.Methods Five patients with lung nodules who underwent CT-guided TFCL before video-assisted thoracoscopic surgery between November 2015 and December 2018 were included. Technical success rates of TFCL and wedge resection were assessed, as well complications and pathological results.Results The technical success rate of TFCL was 100%. Two patients experienced parenchymal hemorrhage around the needle path, and two patients experienced asymptomatic pneumothorax after TFCL. The technical success rate of the wedge resection of lung nodules was also 100%. The pathological diagnoses of the five nodules were minimally invasive adenocarcinoma (n = 3), adenocarcinoma in situ (n = 1), and inflammatory nodule (n = 1).Conclusion CT-guided TFCL is a safe and effective method for the preoperative localization of subfissural lung nodules.
Keywords: transfissural; coil localization; lung nodule; video-assisted thoracoscopic surgery